2000
DOI: 10.1093/emboj/19.21.5762
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus E2 induces senescence in HPV-positive cells via pRB- and p21CIP-dependent pathways

Abstract: Previously published as Susanne I.SchmidA hallmark of human papillomavirus (HPV) associated carcinogenesis is the integration of the viral DNA into the cellular genome, usually accompanied by the loss of expression of the viral E2 gene. E2 binds to and represses the viral promoter directing expression of the E6 and E7 oncogenes. The re-introduction and expression of exogenous E2 in HPV-positive cancer cells results in cellular growth arrest, while growth in the context of exogenous E2 can be restored through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(202 citation statements)
references
References 45 publications
(83 reference statements)
9
189
1
1
Order By: Relevance
“…58 HPVs interfere with both pathways through the activity of the viral E6 and E7 oncoproteins, 3 and reactivation of p53 and pRb activities after E6/E7 inhibition is linked to senescence induction. [35][36][37]57 This reconstitution of p53, as also observed under our experimental conditions, could affect exosome release as p53 can stimulate the TSAP6 and CHMP4C genes, which both enhance exosome formation by unknown mechanisms. [38][39][40][41] In line with this possibility, we found that the enhanced intracellular p53 levels on E6/E7 inhibition were linked to increased expression of both TSAP6 and CHMP4C in HeLa cells.…”
Section: Infectious Causes Of Cancersupporting
confidence: 72%
“…58 HPVs interfere with both pathways through the activity of the viral E6 and E7 oncoproteins, 3 and reactivation of p53 and pRb activities after E6/E7 inhibition is linked to senescence induction. [35][36][37]57 This reconstitution of p53, as also observed under our experimental conditions, could affect exosome release as p53 can stimulate the TSAP6 and CHMP4C genes, which both enhance exosome formation by unknown mechanisms. [38][39][40][41] In line with this possibility, we found that the enhanced intracellular p53 levels on E6/E7 inhibition were linked to increased expression of both TSAP6 and CHMP4C in HeLa cells.…”
Section: Infectious Causes Of Cancersupporting
confidence: 72%
“…E6/E7 transcription from integrated HPV18 genomes can be specifically downregulated via the introduction of E2, a viral gene that is usually disrupted in cervical cancer. Consequences of E2 expression and reactivation of cellular E6/E7 targets have been characterized extensively, and include cell-cycle arrest and subsequent senescence induction Wells et al, 2000). We previously described the transcriptome signature of senescing HPV18-positive HeLa cervical cancer cells using Affymetrix microarrays and a temperature-sensitive E2 protein (Wells et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the F47R-induced senescence pathway appears to be rather distinct than the bovine papillomavirus E2-induced senescence pathway. It was shown earlier that overexpression of p21 CIP by itself could induce senescence in HeLa cells (Wells et al, 2000). In E6 F47R-expressing cells, the sustained activation of p53 signaling pathway and in particular of its target, p21 CIP , may be largely involved in the induction of senescence.…”
Section: Hpv16 E6 Mutant and Cellular Senescence T Ristriani Et Almentioning
confidence: 87%
“…For instance, the transcriptional repression of E6/E7 gene promoter through bovine papillomavirus E2 protein led to reactivation of p53 and pRb pathways and to senescence of HeLa cells (Wells et al, 2000;Horner et al, 2004). Indeed, the repression of 18E7 alone in HeLa cells by expression of the bovine papillomavirus E2 protein induces senescence response that requires activation of endogenous pRB family members but not the p53 pathway (Johung et al, 2007).…”
Section: Hpv16 E6 Mutant and Cellular Senescence T Ristriani Et Almentioning
confidence: 99%
See 1 more Smart Citation